DAMPAK PENGGUNAAN MBANGKING PADA DIGITAL NATIVE MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - maksal mina; Muhammad Fikry (Jurnal Komputer dan Teknologi, 2026)
The rapid development of information technology has accelerated the transformation of banking services into digital-based systems, one of which is mobile banking (Mbanking). This service enables users to conduct financial transactions efficiently without physical interaction with bank offices. This study aims to analyze the effect of perceived usefulness, perceived ease of use, and perceived risk on the intention to use Mbanking among digital native generations using the Technology Acceptance Model (TAM) approach. This research employs a quantitative method with data collected through a Likert-scale questionnaire. The population consists of Generation Z and Millennials in Banda Aceh who use Mbanking services, with a total sample of 70 respondents selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with the assistance of SmartPLS software. The results indicate that perceived usefulness and perceived ease of use have a positive and significant effect on the intention to use Mbanking. In addition, perceived risk also shows a significant influence, indicating that security and trust are crucial factors in adopting digital banking services. Simultaneously, all independent variables significantly affect the intention to use Mbanking. These findings suggest that improving service benefits, ease of use, and system security can enhance users’ interest and sustained use of Mbanking, particularly among digital native groups.